Infectious keratitis in Western New York: a 10-year review of patient demographics, clinical management, and treatment failure - Maretz, Caroline; Atlas, Jason; Shah, Shalini; Sohn, Michael B.; Wozniak, Rachel A. F. (Frontiers in Ophthalmology, 2024)
BackgroundInfectious keratitis (IK) is a blinding disease and an important cause of ocular morbidity. Understanding regional trends in IK are important to understand the epidemiology and clinical outcomes of this disease.MethodsIn this 10-year retrospective review, patient characteristics including sociodemographic factors, medical history, and ocular history were collected as well as the clinical course and outcomes. This study particularly focused on these characteristics as it relates to treatment failure in IK, as defined as requiring more than 2 weeks to heal or surgical intervention, likelihood of having microbiology cultures collected, surgical intervention, and presenting disease severity.Results935 cases of IK were identified at the University of Rochester. Age (p=0.004), history of prior corneal transplant (p=0.009), severe vision loss on presentation (p<0.001), large ulcer size (p=0.001), and fungal (p=0.001) or protozoan (p=0.009) infections were all significantly associated with treatment failure. Both ulcer size (p<0.001) and severity of vision loss (p<0.001) were associated with a higher likelihood of having microbiology cultures as well as surgical intervention. Patients’ whose home address was greater than 60 miles from the University were also more likely to present with a more severe ulcer (p<0.001) and undergo a surgical intervention (p=0.05). In studying the impact of race and ethnicity, Black patients were less likely to receive corneal cultures compared to White patients (p=0.02).ConclusionsThis study defined the patient characteristics and clinical course of patients with IK over 10 years at the University of Rochester providing insight into regional trends of the patient population as well as clinical outcomes.